2020
DOI: 10.2147/idr.s244896
|View full text |Cite
|
Sign up to set email alerts
|

<p>Characterization of <em>SCCmec</em>, <em>Spa</em> Types and Multidrug Resistant of Methicillin-Resistant <em>Staphylococcus aureus</em> Isolates in Ahvaz, Iran</p>

Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most pathogens associated with health care. Molecular typing methods are vital for outbreak investigations of MRSA. The aim of this study was characterization of SCCmec, spa types and multidrug resistant of methicillin-resistant Staphylococcus aureus isolates in Ahvaz, Iran. Methods: A total of 50 MRSA isolates were determined by using the phenotypic method and mecA gene. Antibiotic resistance profile and SCCmec types were screened us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Concerning studies performed in Iran, the prevalence of MRSA ranged from 29% to 40% in non-burn patients and 60% to 90% in burn patients, which indicates a higher prevalence of MRSA strains in burn patients than in non-burn ones. Indeed, these results are in line with our findings (22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Concerning studies performed in Iran, the prevalence of MRSA ranged from 29% to 40% in non-burn patients and 60% to 90% in burn patients, which indicates a higher prevalence of MRSA strains in burn patients than in non-burn ones. Indeed, these results are in line with our findings (22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 93%
“…Other studies in Iran and abroad have reported high levels of resistance in MRSA isolates to different antibiotics, including penicillin, gentamicin, and ciprofloxacin (30)(31)(32). In a study carried out by Moosavian et al (25), all MRSA isolates were sensitive to linezolid and vancomycin (25).…”
Section: Discussionmentioning
confidence: 94%
“…Existence of the mecA gene was investigated using the PCR assay, as earlier defined by Moosavian et al. [ 19 ], The S. aureus ATCC 33591 strain was used as a positive control and S. aureus ATCC 25923 strain was the negative control.…”
Section: Methodsmentioning
confidence: 99%
“…The resistance mechanisms to 尾-lactam antibiotics are associated with the presence of a penicillin-binding protein (PBP2) encoded by the mecA gene in MRSA (Moosavian et al 2020). The affinity of most 尾-lactam reduced due to the overexpression of mecA encoded PBP2a (Hui et al 2020).…”
Section: Reverse Transcription and Qrt-pcrmentioning
confidence: 99%